Pengaruh Pembiayaan Murabahah dan MudharabahTerhadap Perkembangan Usaha Kecil Nasabah BMT Mu’amalah Syari’ah Tebuireng Jombang - Parwati, Indah (BISNIS, 2018)
This study aimed to analyze the influence of murabahah financing and mudharabah in BMT Mu’amalah Syari’ah Tebuireng Jombang on customer’s micro business development. This study used quantitative methods. The datas were analyed using simple linear regression analysis to know the influence between the independent variables and dependent variabels. The research population were 30 murabahah financing’s customers and 19 customers of mudharabah financing. Thus, the entire population of murabahah and mudharabah financing customers were used as the research sample. Data collection techniques used questionnaires and documentation to obtain data on the number of customers and about the development of small business. The results showed that murabahahfinancing and mudharabah had a significant positive effect on the development of small business customers BMT Mu’amalah Syari’ah Tebuireng Jombang.